Gefährliche Forschung? Eine Debatte über Gleichheit und Differenz in der Wissenschaft - Brandtstädter, Susanne; Hinsch, Wilfried (Edition Wissenschaft & Demokratie, 2022)
This volume examines the influence that scientific innovations like artificial intelligence are having on everyday life. By looking at issues like the responsibility of scientists, the application of innovations in public life, and the perception of these innovations in the public sphere, it shines light on the relationship between science and the public sphere.